Synergistic Effects of Physiotherapy and Nutrition in Managing Paediatric Cerebral Palsy - Shukla, Neha; Katiyar, Alka; Shekhar Kumar, Chandra; Dixit, Anamika; Zaidi, Aamena (Journal of Neonatal Surgery, 2025)
Cerebral palsy (CP) is a neurodevelopmental disorder with marked heterogeneity that broadly affects motor function and quality of life in the paediatric population. This narrative review purposes the role of synergism between nutritional interventions and physiotherapy in paediatric CP. Using a review of contemporary relevant literature and clinical evidence, we discuss the possible advantageous role of structuring individualised nutritional inputs in conjunction with specifically structured physiotherapy programs, to enhance outcomes including gross motor function, strength and overall functional capacity. There is a need for integrated approaches for CP management and the review demonstrates how attention to nutritional status can enhance the benefit of physiotherapy treatment and how physiotherapy can enhance nutritional status through improved feeding ability and general metabolic function. We present data to support the notion that these interventions are synergistic and offer clinical recommendations for implementation. A more successful integrating approach to the underlying causes of CP in children will enable health professionals to develop more effective treatment strategies.